The translocation of a chloride channel from the Golgi to the plasma membrane helps plants adapt to salt stress - Rajappa, Sivamathini; Krishnamurthy, Pannaga; Huang, Hua; Yu, Dejie; Friml, Jiří; Xu, Jian; Kumar, Prakash P. (Nature communications, 2024)
A key mechanism employed by plants to adapt to salinity stress involves maintaining ion homeostasis via the actions of ion transporters. While the function of cation transporters in maintaining ion homeostasis in plants has been extensively studied, little is known about the roles of their anion counterparts in this process. Here, we describe a mechanism of salt adaptation in plants. We characterized the chloride channel ( CLC ) gene AtCLCf , whose expression is regulated by WRKY transcription factor under salt stress in Arabidopsis thaliana . Loss-of-function atclcf seedlings show increased sensitivity to salt, whereas AtCLCf overexpression confers enhanced resistance to salt stress. Salt stress induces the translocation of GFP-AtCLCf fusion protein to the plasma membrane (PM). Blocking AtCLCf translocation using the exocytosis inhibitor brefeldin-A or mutating the small GTPase gene AtRABA1b/BEX5 ( RAS GENES FROM RAT BRAINA1b homolog) increases salt sensitivity in plants. Electrophysiology and liposome-based assays confirm the Cl − /H + antiport function of AtCLCf. Therefore, we have uncovered a mechanism of plant adaptation to salt stress involving the NaCl-induced translocation of AtCLCf to the PM, thus facilitating Cl − removal at the roots, and increasing the plant’s salinity tolerance. In Arabidopsis roots, NaCl induces the translocation of AtCLCf from the Golgi to the plasma membrane, mediated by the small GTPase AtRABA1b, where AtCLCf functions as a Cl − efflux channel and confers salinity tolerance to the plant.